Improvement in endothelial cell adhesion and retention under physiological shear stress using a laminin–apatite composite layer on titanium - He, Fupo; Wang, Xiupeng; Maruyama, Osamu; Kosaka, Ryo; Sogo, Yu; Ito, Atsuo; Ye, Jiandong (Journal of the Royal Society interface, 2013)
Apatite (Ap), laminin–apatite composite (L5Ap, L10Ap, L20Ap and L40Ap) and albumin–apatite (AlbAp) composite layers were prepared on titanium (Ti) using a supersaturated calcium phosphate solution supplemented with laminin (0, 5, 10, 20 and 40 μg ml−1) or albumin (800 μg ml−1). With an increase in the concentrations of laminin in the supersaturated calcium phosphate solutions, the amounts of laminin immobilized on the Ti increased. The number of human umbilical vein endothelial cells (HUVECs) adhered to the laminin–apatite composite layers were remarkably higher than those to the untreated Ti, Ap layer and AlbAp composite layer. The number of cells adhered to the L40Ap was 4.3 times the untreated Ti. Moreover, cells adhered to the laminin–apatite composite layers showed significantly higher cell retention under the physiological shear stress for 1 h and 2 h than those to the untreated Ti, Ap layer and AlbAp composite layer. The number of cells remaining on the L40Ap under the physiological shear stress for 2 h was 9.5 times that of the untreated Ti. The laminin–apatite composite layer is a promising interfacial layer for endothelialization of blood-contacting materials.